2017
DOI: 10.5430/jnep.v7n8p19
|View full text |Cite
|
Sign up to set email alerts
|

Oral health beliefs and behaviors of nurse and nurse practitioner students using the HU-DBI inventory: An opportunity for oral health vicarious learning

Abstract: Background: Oral health access to care issues are resulting in curricular changes to train nursing students as oral health educators and providers. However, little data are available concerning their personal oral health beliefs/behaviors. The study purpose was to gather information from nurse and nurse practitioner students regarding their oral health beliefs and behaviors. Methods: Using the Hiroshima University Dental Behavioural Inventory (HU-DBI), survey data were gathered from nurse and nurse practitione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…In the present study, high frequencies of affirmative responses were observed for the receiving of instruction on oral health, more prevalently in the Health block, and especially in relation to the female sex, corroborating studies that highlight women as having greater knowledge and better habits in relation to oral health [1][2][3]5,9,[11][12]. The guidance from the media and other health professionals demonstrated an association with the study groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, high frequencies of affirmative responses were observed for the receiving of instruction on oral health, more prevalently in the Health block, and especially in relation to the female sex, corroborating studies that highlight women as having greater knowledge and better habits in relation to oral health [1][2][3]5,9,[11][12]. The guidance from the media and other health professionals demonstrated an association with the study groups.…”
Section: Discussionsupporting
confidence: 87%
“…Studies that assess the knowledge, attitudes, practices, behavior and self-perception of university students in relation to their oral health have found greater levels of knowledge and positive habits among women, students from public institutions, and those taking courses in the area of health, especially dentistry [3][4][5][6][7][8]. Other studies, meanwhile, have identified limited oral hygiene practices among students from the areas of health, the humanities and the sciences, with such individuals reporting dissatisfaction with their mouths and teeth, and seeking dental care only in case of severe pain or discomfort [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These findings support a thorough completion of the ohr‐interRAI. It has been reported that health promotion and provision of care was influenced by caregivers' own behaviours, attitudes, priority and awareness towards health . In the routine of the care environment, however, oral health had low priority compared to other problems.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that health promotion and provision of care was influenced by caregivers' own behaviours, attitudes, priority and awareness towards health. 71,72 In the routine of the care environment, however, oral health had low priority compared to other problems. This was confirmed by other studies that evaluated attitudes of caregivers towards oral health of clients.…”
Section: Focus Group Discussion With Caregivers To Evaluate Potentmentioning
confidence: 99%
“…[15] In 2000, the Surgeon General featured oral health as а noteworthy part of general health & prosperity since it is essential to the general health of individuals and the population. [50] Additionally, the prevalence rates of obesity in the all-inclusive community have increased substantially in the past 20 years and more alarming is the number of women of childbearing age who are overweight or obese. [51] This expansion in the prevalence of maternal obesity is of great concern as it has been found to be associated with adverse health outcomes affecting the mother during pregnancy.…”
Section: Discussionmentioning
confidence: 99%